PHYTOSOCIOLOGY AND ECOLOGY OF THE NATURAL DRY-GRASS COMMUNITIES ON OAHU, HAWAII - Kartawinata, Kuswata -; Dombois, Dieter Mueller (Research Center for Biology, 1972)
Using the Braun-Blanquet and ordination techniques, nine dry-grass community types were recognized on Oahu,seven of which were dominated by exotic grasses and two by native grasses, Hctcrnpogna eontortus and Erarjrostis variabilis.These community types occured in summer-drought, summer-dry and humid climates.The distribution of certain community types could be correlated directly with rainfall and soil pH. In the summer-drought climate the occurrence of the community types was related to topography,wind exposure, rockiness of the land surface and stoniness of the soil.The nine community types were not related to the established soil series, organic matter content and watsr retaining capacity of the surface soils.Three distinct soil-water regimes were recognized in five community types: drought, dry and wet types.Seasonal variations in soil-water content were correlated closely with the rainfall pattern.The introduction and spread of exotic species resulted in a gradual disappearance of the native grass communities in the summer-drought zone. In the summer-dry zone, Grevillea robiista. trees and Meliiiis minutiflora grass mats were invading the Rhynchelytrum repens community. Artdropogon virginiciis, introduced in 1932, formed a wide spread herbaceous community in the humid zone. In some places, this community was invaded by Dicranopteris linearis fern mats and trees of Acacia, koa or Metrosideros collina. Fire in both the summer-dry and humid zones maintained and extended the grass communities.